Treatment Efficacy of Sacral Nerve Stimulation in Slow Transit Constipation: A Two‐Phase, Double‐Blind Randomized Controlled Crossover Study. (May 2015) - Dinning, Phil G; Hunt, Linda; Patton, Vicki; Zhang, Teng; Szczesniak, Michal; Gebski, Val; Jones, Mike; Stewart, Peter; Lubowski, David Z; Cook, Ian J
Abstract : Objectives: Sacral nerve stimulation (SNS) is a potential treatment for constipation refractory to standard therapies. However, there have been no randomized controlled studies examining its efficacy. In patients with slow transit constipation, we evaluated the efficacy of suprasensory and subsensory SNS compared with sham, in a prospective, 18‐week randomized, double‐blind, placebo‐controlled, two‐phase crossover study. The primary outcome measure was the proportion of patients who, on more than 2 days/week for at least 2 of 3 weeks, reported a bowel movement associated with a feeling of complete evacuation. Methods: After 3 weeks of temporary peripheral nerve evaluation (PNE), all patients had permanent implantation and were randomized to subsensory/sham (3 weeks each) and then re‐randomized to suprasensory/sham (3 weeks each) with a 2‐week washout period between each arm. Daily stool dairies were kept, and quality of life (QoL; SF36) was measured at the end of each arm. Results: Between November 2006 and March 2012, 234 constipated patients were assessed, of whom 59 were willing and deemed eligible to participate (4 male; median age 42 years). Of the 59 patients, 16 (28%) responded to PNE. Fifty‐five patients went on to permanent SNS implantation. The proportion of patients satisfying the primary outcome measure did not differ between suprasensory (30%) and sham (21%) stimulations, nor between subsensory (25%) and sham (25%) stimulations. There were no significant changes in QoL scores. Conclusions: In patients with refractory slow transit constipation, SNS did not improve the frequency of complete bowel movements over the 3‐week active period.